The Influence of Patient Baseline Data and Mental Health in Predicting Outcomes after Hip Arthroscopy for Femoracetabular Impingement Syndrome: A Prospective Cohort Analysis. Issue 7 (29th July 2019) - Lynch, Thomas Sean; Cossell, Charles Edward; Strnad, Greg; Zajichek, Alex; Pignolet, Isabel; Kattan, Michael W.; Jones, Morgan H.; Spindler, Kurt P.; Rosneck, James T.
Objectives: Patient factors, including mental health, activity level, sex, and smoking, have been found to be more predictive of preoperative hip pain and function than are intra-articular findings during hip arthroscopy for femoroacetabular impingement (FAI); however, little is known about how these patient factors or pathologic findings may influence postoperative rehabilitation, recovery, and final outcome. We hypothesized that patient factors, including mental health, would more strongly correlate with patients' one-year patient-reported outcome measures (PROMs) of hip pain and function compared to the extent of the intra- or extra-articular pathology (chondral damage, labral tear, cam, or pincer deformities) in patients undergoing surgery for FAI. Methods: A prospective cohort of patients undergoing hip arthroscopy for FAI were electronically enrolled between February 2015 and July 2017. Baseline PROMs were collected, including Hip disability and Osteoarthritis Outcome Score (HOOS) for pain, HOOS-Physical Function Shortform (HOOS-PS), Veterans RAND 12-Item Health Survey (VR-12), and University of California-Los Angeles (UCLA) Activity Score. Surgeons documented intra-articular operative findings and treatment via an all-electronic capturing system on their cellular device at the time of surgery. Proportional-odds logistic regression models were built for each one-year PROM of interest using baseline patient and surgical characteristics. However, instead of using the baseline HOOS-Pain and HOOS-PS scores as predictors, the improvement score from baseline to one year was used for the respective models. Risk factors included patient characteristics and intraoperative anatomic and pathologic findings. Results: During the study period, 555 patients underwent arthroscopic hip procedures with 494 patient undergoing hip arthroscopy for FAI. Of this FAI cohort, 489 had baseline PROMs, and 377 (77.7%) completed both preoperative and one-year PROMs. The median patient age was 33 years, mean body mass index was 25.5 kg/m2, and 72% were female. Multivariate analyses demonstrated that baseline patient characteristics are the main drivers of each PROM, and baseline PROM scores, the improvement in those scores, and smoking status have the most influence (Figure One). In terms of mental health, subjects with worse baseline VR-12 scores had less PROM improvement. For intra-operative findings, grade 3/4 articular cartilage damage was associated with worse pain and PS scores compared to those with no cartilage damage. Conclusion: This is the first prospective cohort analysis of hip arthroscopy for FAI evaluating the influence of baseline characteristics on patient outcomes at one year. This analysis was uniquely modeled to adjust for these identified patient factors to allow for accurate interpretation of their effect on the patient's treatment. Patient factors, including score improvement, mental health, and smoking, are more predictive of one-year patient-reported outcomes of hip pain and function (as measured by HOOS) than are intra-articular findings (e.g., status of the labrum or articular cartilage) during hip arthroscopy for FAI. This information can be useful during preoperative education to help manage patients' expectations after their arthroscopic procedure and guide their care.